Analytical solution to the MHD flow of micropolar fluid over a linear stretching sheet - Siddheshwar, Pradeep G.; Mahabaleshwar, U.S. (Zielona Góra: Uniwersytet Zielonogórski)
The flow due to a linear stretching sheet in a fluid with suspended particles, modeled as a micropolar fluid, is considered. All reported works on the problem use numerical methods of solution or a regular perturbation technique. An analytical solution is presented in the paper for the coupled non-linear differential equations with inhomogeneous boundary conditions.
Keywords: differential equation; stretching sheet; MHD; micropolar fluid; linear stretching sheet